Epidemiology of Osteoporosis in Patients with Chronic Obstructive Pulmonary Disease in Taiwan - Kuang-Ming Liao; Chuan-Wei Shen; Kai-Lin Chiu; Chun-Hui Lu; Chih-Wun Fang; Chung-Yu Chen (Springer, 2024)
Abstract Background Chronic obstructive pulmonary disease (COPD) is a preventable and treatable chronic condition characterized by progressive, partially reversible airflow obstruction. Osteoporosis represents a significant comorbidity in individuals with COPD. However, the incidence and prevalence of osteoporosis among the COPD population remain unclear in Taiwan. Therefore, our objective is to investigate the incidence and prevalence of osteoporosis in patients with COPD. Methods In this cross-sectional study, we enrolled a COPD population retrieved from the Taiwan National Health Insurance Research Database (NHIRD) spanning the years 2003 to 2016. Osteoporosis patients were identified using diagnosis codes. The study included newly diagnosed COPD patients from 2003 to 2016. The case group comprised patients who developed osteoporosis or osteoporotic fractures after their COPD diagnosis. We calculated the prevalence and incidence of osteoporosis in individuals with COPD and conducted trend tests. Results A total of 1,297,579 COPD patients were identified during the period from 2003 to 2016, with 275,233 of them in the osteoporosis group. The average prevalence of osteoporosis among individuals with COPD was 21.21% from 2003 to 2016 in Taiwan. The number of osteoporosis cases increased from 6,727 in 2003 to 24,184 in 2016. The prevalence of osteoporosis among COPD patients increased from 3.62% in 2003 to 18.72% in 2016. The number of osteoporosis cases among individuals with COPD continued to rise over the years, reaching its highest point in 2016 with 24,184 new cases. The incidence of osteoporosis fluctuated during the study period but generally remained around 3,000 cases per 100,000 person-years. Notably, there was a significant upward trend in incidence from 2003 to 2006, after which the trend stabilized and remained relatively constant. Conclusions Our study highlights an increase in both the prevalence and incidence of osteoporosis in individuals with COPD. Given the significant medical, economic, and social implications associated with osteoporosis, a comprehensive and robust assessment of its healthcare burden can offer valuable insights for healthcare system planning and policymaking.